Optimization Control Access User Use Access Control List Based Mikrotik On Amami Event Organizer - Ibnu Ubaedila; Ida Farida (Publikasi Indonesia, 2026)
Technological developments are not only used as a medium for disseminating information but can also be used as a medium for marketing products and services. Amami event organizer is one of the companies engaged in providing services for exhibition events in the city of Cirebon in particular, this company has utilized internet services as part of their service marketing strategy. This study aims to optimize user access control using a Mikrotik-based Access Control List (ACL) to enhance network security and efficiency. Therefore, we need a method that can control internet access effectively and efficiently, the solution is to use the access control list method. The access control list method is a method that is specifically designed to carry out rules in determining the number of packets that may be used and passed by the router or should not be passed. Based on the results obtained from hypothesis testing, it is found that the T count is 37.291 and the comparison of the T table value is 1.724. So with the results that have been found, it can be concluded that Ho is rejected and H1 is accepted. It can be concluded that optimizing user access control by using access control lists can work effectively and is well received by the amami event organizer company. In conclusion, the implementation of ACL using Mikrotik proves to be an effective solution for optimizing user access control and strengthening network security in organizational environments.